مستوى التّنمر المدرسي لدى تلاميذ المرحلة المتوسطة - أميطوش, موسى (جامعة الوادي - University of Eloued, 2021)
هدفت الدّراسة إلى معرفة مستوى التنمر المدرسي لدى تلاميذ المتوسطات والتعرف على الأشكال الأكثر انتشارا في هذه المرحلة، وكذلك الكشف عن الفروق في مستوى التنمر بدلالة الجنس والعمر، تكوّنت عيّنة الدّراسة من (167) تلميذ وتلميذة، استخدم الباحثان مقياس التّنمر الذي أعده "محمد علي الصبحين" (2013)، وبعد التحليل الإحصائي توصلنا إلى النتائج التالية: - مستوى التّنمر المدرسي لدى تلاميذ المرحلة المتوسطة متوسط، وبلغت الدرجة الكلية للاستقواء على عينة الدراسة نسبة (33.06%) ضمن درجة استقواء كبيرة، ويتواجد التّنمر لدى أفراد العينة على عدّة أشكال، إذ جاء التّنمر الجسمي في المرتبة الأولى، تلاه اللّفظي، ثم الاجتماعي، وبعدها التنمر على الممتلكات، وأخيرا الجنسي. - لا توجد فروق دالة إحصائيا في التّنمر المدرسي بدلالة الجنس. - توجد فروق دالة إحصائيا في التّنمر المدرسي بدلالة العمر، لصالح الأقل سنا . Abstract: The study aimed to know the level of school bullying among students of the averages and to identify the most prevalent forms at this stage, as well as to reveal the differences in the level of bullying in terms of gender and age. The study sample consisted of (167) male and female students. (2013); and after statistical analysis, we reached the following results: - The level of school bullying among middle school students is average, and the total degree of bullying on the study sample was (33.06%) within a large degree of bullying. And then property bullying, and finally sexual. - There were no statistically significant differences in school bullying as a function of gender. - There are statistically significant differences in school bullying as a function of age, in favor of the younger age group.
مقال
Keywords: تنمر ; تنمرمدرسي ; تلاميذ المرحلة المتوسطة; Bullying; school bullying; middle school students